High-dose-rate interstitial brachytherapy in head and neck cancer: do we need a look back into a forgotten art – a single institute experience - Bhalavat, Rajendra; Chandra, Manish; Pareek, Vibhay; Nellore, Lalitha; George, Karishma; P., Nandakumar; Bauskar, Pratibha (Journal of Contemporary Brachytherapy, 2017)
Purpose : To evaluate the treatment outcomes with high-dose-rate (HDR) interstitial brachytherapy (HDR-BRT) in head and neck cancers (HNC). Material and methods : Fifty-eight patients with HNC as per American Joint Committee on Cancer (AJCC) TNM staging criteria were analyzed retrospectively between 2008 and 2015. Forty-two patients received external beam radiotherapy (EBRT) with HDR-BRT and 16 patients received BRT alone. The survival was calculated with respect to median biological equivalent doses (BED) and median 2 Gy equivalent dose (EQD 2 ), keeping / = 10 for tumor. Loco-regional control and disease free survival was assessed. Results : The median follow-up period was 25 months (2-84 months). The disease-free survival (DFS) probability at year 1 was 82.7%, and 68% at year 7. The overall survival probability was 91.3% at year 1 and 85.8% at year 7. The local control rate was 70%. The rate of recurrence was 30%. Distant metastasis rate was 17.2%. The median BED and EQD 2 , respectively, were 86.78 Gy and 71.6 Gy. The DFS was 74.1% and 75.9% in patients receiving a dose more than median BED and EQD 2 , respectively, and was 64.8% and 61.5% for less than the median dose. Conclusions : The overall outcome was good with implementation of HDR-BRT used alone or as boost, and shows DFS as better when the dose received is more than the median BED and median EQD 2 . The role of HDR-BRT in HNC is a proven, effective, and safe treatment method with excellent long term outcome as seen in this study, which reflects the need for reviving the forgotten art and science of interstitial brachytherapy in HNC.